PENDEKATAN KOGNITIF DALAM PEMBELAJARAN KAIDAH NAHWU UNTUK PENUTUR NON-ARAB - Yuni Amalia; Wafiq Azizah Ashari; Syifa Wiri Tanaya; Muhammad Zaky Fahmi (Jurnal Sathar, 2025)
This study aims to describe the implementation of the cognitive approach in learning nahwu rules for non-Arabic speakers and analyze its effectiveness in improving students' understanding. The cognitive approach is used to optimize students' thinking processes, help them build concepts actively, and link new information to existing cognitive structures. This study uses a descriptive qualitative method with data collection techniques through observation, literature studies, and documentation analysis. The results of the study indicate that cognitive strategies such as mind mapping, sentence pattern analysis, meaning elaboration, and problem-based learning are effective in helping students understand nahwu rules in depth. In addition, this approach is able to improve long-term memory, analytical skills, and students' learning motivation. However, the success of the implementation is greatly influenced by factors such as students' cognitive readiness, teacher competence, availability of learning media, and available learning time. In conclusion, the cognitive approach makes a positive contribution to the mastery of nahwu rules for non-Arabic speakers, as long as it is supported by systematic and creative learning strategies.